ISOLASI Rhizopus oligosporus DAN Rhizopus stolonifer PADA TIGA TEMPE DI KELURAHAN JATIMAKMUR, BEKASI - Qurrota Aýun Saunin; Lulu Ul Janah (Universitas Bengkulu, 2022)
Tempeh is a typical Indonesian food product made from soybeans and fermented using Rhizopus sp. The manufacture of tempeh is carried out from generation to generation traditionally so that it is possible for the emergence of different microorganisms. This study aims to isolate and identify R. oligosporus and R. stolonifer in three tempeh in Jatimakmur, Bekasi. The samples used were from three types of tempeh from different locations. The method used is direct plating. Observations were carried out macroscopically by observing the color of conidia and mycelium. Microscopically it was carried out using slide culture by observing the shape of spores, columellae, sporangiospore and hyphae. Data are presented in the form of figures and tables. The analyzed descriptively qualitatively. The results showed that from three tempeh samples coming from different locations, two tempeh samples were similar R. oligosporus and the others were similar R. stolonifer.